About The Concept Of "Translation Strategies" In The Translation Studies - Khudaybergenova, Zilola (The journal of contemporary issues in business and government, 2021)
In modern translation studies, the phrase "translation strategy" is widely used to describe the translation process. This article analyzes the concept of "translation strategy", various definitions of this term, the reasons for the emergence of this concept. In a number of cases, the specific content of a given concept is generally unclear. The same researchers put different content into this phrase. "Translation strategy" can indicate principled approaches to solving particular problems within the framework of a general task. Use the phrase "translation strategy" to refer to the methods used to achieve the goals formulated when choosing a "translation strategy". In addition, in many cases, this phrase denotes specific translation techniques. On the other hand, the phrase “translation strategy” is used to denote general translation approaches in translation. The article also discusses the principles and content of the translation strategy. The survivability factors of the translation strategy are interpreted.